Diffusion approximation of stochastic Markov models with persistent regression - Koroliuk, D.; Korolyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Sequences of sums of identically distributed random variables forming a homogeneous Markov chain are approximated by a time-discrete autoregression process of Ornstein-Uhlenbeck type.